The coherence of democratic peace-building - Peter Burnell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Recent attention has focused on the difficulties of establishing `coherence' between humanitarian relief aid in complex emergencies and the objective of ending violent conflict. This paper introduces a parallel problem: absence of total synergy between making peace and building democracy. A widely held assumption in the international community is that in post-conflict situations peace-building and democratization are virtually synonymous; creating the conditions for the one does so for both, the two processes will be reciprocal and mutually supportive. This suggests the policy issues will be simple. But the reality could be very different. Choices have to be addressed between requisites for peace and conditions for democracy; over the different implications for peace of competing designs for democracy; and over the kind of `democracy' and its relation to other essential developments like state-building Institutional crafting is important; but matters concerning civil society and political culture must be addressed too. Governance and welfare considerations will bear on both peace and democracy but not necessarily in identical ways. There are temporal choices to address as well; the order of passage from peace to stable democracy may be as significant as the rites of passage. The belief that the well-known theory of a democratic peace in international relations has its complement in a democratic domestic peace looks plausible, but `getting there' after conflict will be challenging. Issues of strategy and policy are most problematic where peace, prosperity and democracy have all been deficient—a situation common to many societies. – democratization ; conflict ; democratic domestic peace
Keywords: H56; O19; F50; H11; N40; 330